Role of structural distortion in stabilizing electrosynthesized blue emitting phosphorene quantum dots - Valappil, Manila Ozhukil; Joshi, Krati; John, Lisa; Krishnamurthy, Sailaja; Jana, Bikash; Patra, Amitava; Pillai, Vijayamohanan K.; Alwarappan, Subbiah (Journal of Physical Chemistry Letters, 2019)
Luminescent phosphorene quantum dots (PQDs) have emerged as fascinating nanomaterials for potential applications in optoelectronics, catalysis, and sensing. Herein, we investigate the structural distortion of black phosphorus (BP) under an applied electric field to yield blue luminescent PQDs [average diameter 8 +/- 1.5 nm (N = 60)]. The electrosynthesized PQDs exhibit photoluminescence emission independent of excitation wavelength with 84% quantum efficiency. Structural distortion that occurred during the transformation of BP to PQDs is confirmed by results obtained during transmission electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. Further, using first-principles-based density functional theory, calculations on oxygenated and nonoxygenated PQDs augment the experimental observations that an optimum oxygen content maintains the structural integrity of PQDs, above which the structural robustness of PQDs is drastically diminished.

Rational design of hydrophobic Cu/CuO electrodes for electrochemical oxygenation of tetralin: a strategic approach - Cherukuthota, Sri Vidya; Mathew, Elizabeth; Verma, Tushar Singh; Joshi, Krati; Selvaraj, Kaliaperumal (ChemSusChem, 2025)
Electro-organic synthesis presents a sustainable and practical alternative to traditional organic synthesis methods, which typically utilize harsh reagents and require energy-intensive conditions. Nevertheless, the challenge of achieving satisfactory conversion and selectivity rates in electrocatalytic oxidation using a non-platinum group metal (PGM) catalyst pair still needs to be addressed. This study demonstrates the application of a non-PGM-based catalyst pair for the electrocatalytic oxidation of tetralin to 1-tetralone, a highly demanded raw material in the pharma industry. Copper electrodeposited on teflonated carbon paper combined with copper foam as the electrocatalyst pair has demonstrated impressive conversion and selectivity ratios to electro-synthesize 1-tetralone at room temperature and atmospheric pressure. The optimal choice of a non-PGM catalyst, ideal mass loading, and a unique electrode configuration resulted in an ultimate conversion of about 99% of tetralin and 1-tetralone selectivity -93.7%, yield -92.6%. The reaction pathway associated with the electrochemical phenomena is supported by first principles-based density functional theory calculations and X-ray photoelectron spectroscopy of the electrocatalyst. This process has exceptional performance that can be adapted for a wide range of substrates and is straightforward, ambient, reagent-free, scalable, and therefore beneficial for industrial use. Therefore, initiatives have been taken in this direction.
Keywords: C-H activation; Copper; electrochemical oxidation; non-PGM electrocatalysts; tetralin; Tetralone